GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Hidayat, Wahyu -; Lailiyah, Elliv Hidayatul; Hayat, Ardiansyah Ahsanul (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
This study aims to determine the effect of leadership style and work motivation on cleaning service performance with job satisfaction as a moderating variable. This research was conducted at the Cleaning service PT. Pelindo Daya Sejahtera work unit Primasatya Husada Citra Hospital Surabaya. The population of this study was 76 respondents because the population was not more  than 100 respondents, so the authors took 100% of the population as a sample in this study. In this study, a questionnaire was tested using validity and reliability tests, while the data analysis used in this study used the classical assumption test and the MRA (Moderated Regression Analysis) test. The results of this study indicate that the leadership style variable has an effect on performance of Cleaning service PT Pelindo Daya Sejahtera Work unit Primasatya Husada Citra Hospital Surabaya. Work motivation has a positive effect on cleaning service performance. Job satisfaction moderates by strengthening the influence of leadership style on cleaning service performance. Job satisfaction moderates by strengthening the effect of work motivation variables on cleaning service performance.